Improving Students’ Reading Ability of Descriptive Text by using Small Group Discussion - Lisematul Faizeh; Hanif Maulaniam Sholah (Institute Agama Islam Al-Qolam Malang, 2020)
In this research, the researcher applied Small Group Discussion to overcome the problems that were faced by the students. This research was conducted in order to improve students’ reading ability in descriptive text through Small Group Discussion at the seventh grades of MA Al-Hisi Ringinsari Sumbermanjing Wetan 2016-2017. In conducting this research, the researcher used Classroom Action Research (CAR) as the method of research. The researcher conducted this research in two cycles. Each cycle consisted of three meetings. The researcher used Small Group Discussion to create comfortable atmosphere during teaching and learning process of reading, and more importantly to improve the students’ reading ability especially on reading descriptive text. The subject of this research was the students of seventh grade at MA Al-Hisi Ringinsari Sumbermanjing Wetan 2016-2017 on academic year especially VII IPA class. The instruments to collect the data were interview, observation checklist, and reading test. The result of the research showed that by using Small Group Discussion in teaching reading descriptive text. The researcher could improve the student’s reading ability especially descriptive text. Their responses showed that they were interested to learn reading subject because they felt easier to read using Small Group Discussion.